2019
DOI: 10.3390/w11102131
|View full text |Cite
|
Sign up to set email alerts
|

A Classification Method for Fish Swimming Behaviors under Incremental Water Velocity for Fishway Hydraulic Design

Abstract: In fishway design, the combination of fish swimming behaviors and suitable fishway hydraulic characteristics increases the fish passage efficiency. In this study, the most representative grass carp among the “four major Chinese carps” was selected. Under conditions similar to the time period for feeding migration, juvenile grass carps were targeted to study the swimming characteristic indicators (i.e., critical and burst swimming speeds) and swimming behaviors that were closely associated with fishway hydrauli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Morphological adaptation of stream fish is mostly on the locomotion part, consisting of a variation on the abdominal shape, caudal regions, and fins (Shuai et al, 2018;Hanif et al, 2019). The slender body of stream fish is crucial to enhance the ability to swim against the stream (Mu et al, 2019;Wagle et al, 2015). Dunn et al (2020) reported population morphological variations of Galaxias brevipinnis, Galaxias gollumoides, and Galaxias Vulgaris in lotic habitats have a slender body to their lentic-habitats counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological adaptation of stream fish is mostly on the locomotion part, consisting of a variation on the abdominal shape, caudal regions, and fins (Shuai et al, 2018;Hanif et al, 2019). The slender body of stream fish is crucial to enhance the ability to swim against the stream (Mu et al, 2019;Wagle et al, 2015). Dunn et al (2020) reported population morphological variations of Galaxias brevipinnis, Galaxias gollumoides, and Galaxias Vulgaris in lotic habitats have a slender body to their lentic-habitats counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers [17][18][19][20], when studying swimming characteristics in several species from the family of Cyprinidae, noted significant differences between individuals of different sizes and species; with increasing age and size of the fish's body, the swimming characteristics of the individual also increase, while it was established [21] that the water flow velocity and substrate are the main factors affecting the choice of biotope, while the first of them is considered the most significant. This pattern explains the distribution of a larger percentage of large fish from the family Cyprinidae at a high-velocity section of the watercourse -No.…”
Section: Discussionmentioning
confidence: 99%
“…Between 6 Â 10 À4 N and fish thrust at maximum sustained speed (6 Â 10 À3 N), fish were considered to be in an "endurance state". Maximum sustained speed corresponds to the maximum speed reachable in endurance swimming: i.e., an activity that can be maintained over a long period of time and uses only aerobic muscle fibers (Mu et al 2019). Above the maximum sustained speed, the fish was in a "burst state".…”
Section: Fish Navigation and Propulsion Force Estimationmentioning
confidence: 99%
“…Above the maximum sustained speed, the fish was in a "burst state". Burst swimming is swimming behaviour that cannot be maintained for a long time, that requires both aerobic and anaerobic muscle fibers, and can correspond to unsuitable predation conditions or breaking through water flow barriers (Mu et al 2019).…”
Section: Fish Navigation and Propulsion Force Estimationmentioning
confidence: 99%